Transformation of Udmurt Geographical Names - L. E. Kirillova; M. A. Samarova (Научный диалог)
The ways of transfer into Russian language of Udmurt place names, mainly the names of settlements of the Udmurt Republic and adjacent territories where the Udmurt people live are considered. The relevance of the study is justified by the fact that the language contacts of the Udmurts with the Russians could not but affect the toponymy of the region, and in the official documents the Udmurt names of settlements are recorded in the form adapted by the Russian language. The analysis of the extinct and currently functioning place names allowed the authors to testify that in the process of historical development and interaction of languages, most of the Udmurt geographical names are subject to various modifications. Different types of transformations are identified and studied: transliteration, phonetic, morphological and lexical transformations, reduction (simplification), translation or calking, rethinking, renaming (denomination). It is shown that these changes are not random, but are subject to the general laws of the language. The authors conclude that the main reason for the modification of Udmurt place names in the transmission to the Russian language is the difference in typological features of Slavic and Finno-Ugric languages. There are many examples to prove that in development of foreign names by the Russian language there is a complete or partial transformation of foreign elements of the source language, in addition, their own elements are added.